2017
DOI: 10.1021/acs.jpcb.7b02693
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Vibrational Dephasing Time and Energy Gap Fluctuations

Abstract: Dephasing processes are present in basically all applications in which quantum mechanics plays a role. These applications certainly include excitation energy and charge transfer in biological systems. In a previous study, we have analyzed the vibrational dephasing time as a function of energy gap fluctuation for a large set of molecular simulations. In that investigation, individual molecular subunits were the focus of the calculations. The set of studied molecules included bacteriochlorophylls in Fenna-Matthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Therefore, we believe that the main contribution to the enhancement of the Raman signal arises from the CT transitions borrowing the intensity from the exciton resonances in MoS 2 . The 10–20% decrease in dephasing times of both studied pyridine vibrational modes suggests the formation of CT states in the vicinity of MoS 2 , as well as the generation of excitons …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, we believe that the main contribution to the enhancement of the Raman signal arises from the CT transitions borrowing the intensity from the exciton resonances in MoS 2 . The 10–20% decrease in dephasing times of both studied pyridine vibrational modes suggests the formation of CT states in the vicinity of MoS 2 , as well as the generation of excitons …”
Section: Discussionmentioning
confidence: 95%
“…The 10−20% decrease in dephasing times of both studied pyridine vibrational modes suggests the formation of CT states in the vicinity of MoS 2 , 58 as well as the generation of excitons. 59 Note that the increase of the CARS signal at 999 cm −1 from the pyridine−ethanol complexes can also be attributed to other mechanisms in addition to the surface enhancement by MoS 2 . For example, a direct pyridine bond with MoS 2 may result in a similar blue-shift of the ring breathing mode as in the case of the pyridine−ethanol complexes.…”
Section: ■ Discussionmentioning
confidence: 99%
“…To better understand the high degree of similarity of the results in Figure for the two different noise autocorrelation time of 1 and 50 fs, we turn to estimates of the dephasing time. The determination and analysis of dephasing times in molecular functions has been a topic of recent investigations. , For specific exciton and charge transfer systems, a clear relation was found between the energy gap fluctuations and an estimate of the dephasing time. The investigated charge transfer systems in those numerical studies using a multiscale approach were DNA, photolyase, and cryptochrome . It was found that the energy gap fluctuations in these systems ranged from 0.15 to 0.35 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Further, because it solves the many-body problem exactly, it can access regimes that are challenging for other methods such as those encountered when the nuclear mass is small (where the Born-Oppenheimer approximation and even the very concept of a potential energy surface fails) or when the electron correlation is large. These simulations complement recent efforts to capture electronic decoherence dynamics in molecules using semiclassical approximations [2,15,16,18,29], the multiconfiguration time-dependent Hartree method (MCTDH) [30][31][32] and a recently proposed generalized theory for the timescale of the electronic decoherence in the condensed phase [33].…”
Section: Introductionmentioning
confidence: 87%
“…In turn, explicit approaches offer a detailed description of the nuclear dynamics albeit at an approximate level. Approximations that have been employed to model decoherence include surrogate Hamiltonians [11], path-integral techniques [12], frozen Gaussian approaches [13], semi-classical methods [14] and quantum-classical methods [2,[15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%